Analysis of the Protection Performance of Face Guard for Large Mining Height Hydraulic Support - Lirong Wan; Shuai Zhang; Zhaosheng Meng; Yunyue Xie (Shock and Vibration)
With the increase of mining height, the problem of coal wall spalling in the working face gradually worsens. Hydraulic support and its face guard structure are the key pieces of equipment to restrain the coal wall spalling. However, at present, the hydraulic jack is mostly considered as rigid in the analysis of protection mechanism. This simplification cannot effectively reflect the true bearing state of the face guard. In order to improve the accuracy of analysis, this study considers the face guard jack as a flexible spring and establishes a rigid-flexible coupling analysis model of the face guard mechanism. First, based upon the multibody dynamics software ADAMS®, the multibody numerical model of the face guard of the hydraulic support was established. The influence of the two kinds of structures on the coal wall disturbance was analyzed and compared. Then, the rigid model was meshed. The hydraulic jacks were equivalent to the spring system, and the rigid-flexible coupling model was established. Based upon the application load on different positions of the rigid-flexible model, the load-bearing characteristics and hinge point force transfer characteristics of the two face guards were analyzed. The results show that the support efficiency of the integral type was higher than that of the split type. In the vertical support attitude, the dynamic disturbance of the coal wall, produced by the two kinds of face guards, was small. The four-bar linkage effectively improved the ultimate bearing capacity of the integral face guard. The results provide theoretical support for the design and optimization of the face guard.